2022
DOI: 10.3390/healthcare10081414
|View full text |Cite
|
Sign up to set email alerts
|

Food Intake Changes and Their Impact on Quality of Life in Spanish Citizens with and without COVID-19 during Lockdown

Abstract: The pervasive impact of the COVID-19 pandemic is just beginning to be analyzed. To date, only a handful of these studies have investigated the relationship between an individual’s quality of life (QoL) and their changes in food intake due to the virus (from the associated symptomatology of diagnosis to the universal impact of lockdown on individual lives, regardless of a person’s health status). Therefore, the purpose of this study is to identify changes in food intake resulting from the pandemic and the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Their results showed that eating habits characteristic of the MD (i.e., a higher fruit, vegetable, and bean intake, a lower sweet consumption, having breakfast more often, and having family meals) were related to lower sleep-related problems. It is possible that the consumption of certain MD components facilitates an adequate sleep duration (diminishing sleep-related problems) and, therefore, a higher HRQoL [ 53 , 54 ]. Lastly, breakfast (an important component of the MD) has been associated with greater psychosocial health in Spanish preschoolers, children, and adolescents [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that eating habits characteristic of the MD (i.e., a higher fruit, vegetable, and bean intake, a lower sweet consumption, having breakfast more often, and having family meals) were related to lower sleep-related problems. It is possible that the consumption of certain MD components facilitates an adequate sleep duration (diminishing sleep-related problems) and, therefore, a higher HRQoL [ 53 , 54 ]. Lastly, breakfast (an important component of the MD) has been associated with greater psychosocial health in Spanish preschoolers, children, and adolescents [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%